(NsOC)QÆALXNO(B-(NPSIHOLOGÆ^NIJ PRAKTIKUM (B/s)E - (NpOD[IWALK)QÆNA(B, (Nw(B. æ.,s)E; (NdEMENTX)QÃWA(B, (Nk(B. (Ng(B.s)E; (NoDESXKIJ NAC)QÆONALXNIJ UNÆWERSITET ÆMENÆ æ(B. æ. (NmE^NIKOWAs)E; )Qæ(NNSTITUT MATEMATIKI(B, (NEKONOMÆKI TA MEHANÆKI WÆDDÆLENNQ PSIHOLOGÆÇs)E (NkAFEDRA SOC)QÆALXNOÇ Æ PRIKLADNOÇ PSIHOLOGÆÇs)E ((NkI)QÇW (B:s)E (Nknt(B,s, 2025)
(NsOC)QÆALXNO(B-(NPSIHOLOGÆ^NIJ PRAKTIKUM PROPANUÃ WARÆANTI LABORATORNIH ROBÆT DLQ STUDENTÆW PSIHOLOGÆW(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NsOC)QÆALXNA PSIHOLOGÆQs)E; (NPSIHOLOG)QÆ^NÆ DOSLÆDVENNQs)E; (NSOC)QÆALXNA PSIHOLOGÆQs)E; (NOSOBIST)QÆSTXs)E; (NGENDERN)QÆ ROLÆs)E; (NGRUPOWA TERAP)QÆQs)E; (NSOC)QÆOKULXTURNA REGULQCÆQs)E